Overview of DNA Sequencing Strategies - Shendure, J.A.; Porreca, G.J.; Church, G.M.; Gardner, A.F.; Hendrickson, C.L.; Kieleczawa, J.; Slatko, B.E.
Efficient and cost-effective DNA sequencing technologies are critical to the progress of molecu-lar biology. This overview of DNA sequencing strategies provides a high-level review of seven distinct approaches to DNA sequencing: (a)dideoxy sequencing; (b)solid phase sequencing; (c)sequencing-by-hybridization; (d)mass spectrometry; (e)cyclic array sequencing; (f)micro-electrophoresis; and (g)nanopore sequencing. Other platforms currently in development are also briefly described. The primary focus here is on Sanger dideoxy sequencing, which has been the dominant technology since 1977, and on cyclic array strategies, for which several competi-tive implementations have been developed since 2005. Because the field of DNA sequencing is changing rapidly, this unit represents a snapshot as of September, 2011.